The Students’ Perception of The Media Used by Teacher in Teaching English Students of SMK 1 Tirtamulya - Hadiwijaya, Rangga (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study investigates students' perceptions of instructional media employed in English language teaching at SMK 1 Tirtamulya Karawang. Despite the recognized significance of media in educational settings, there remains limited research addressing its comprehensive impact within vocational school contexts. Adopting a qualitative descriptive method, data were obtained through classroom observations and interviews with 18 tenth-grade students and their English teacher. The findings indicate that tools such as whiteboards, textbooks, laptops, and speakers contribute positively to students' enjoyment, engagement, and comprehension, while also supporting pronunciation and vocabulary development. Nevertheless, some students expressed negative perceptions, citing disinterest or fear of making mistakes. The research underscores the dual nature of media, both aiding and potentially hindering learning, and highlights the necessity for thoughtfully chosen media tailored to student needs. The implications suggest that educators should incorporate a variety of interactive tools—such as gamification or virtual reality—to cater to diverse learning preferences. Future studies are encouraged to apply mixed-method approaches to further evaluate media effectiveness. This research adds to the discourse on educational technology by addressing gaps in vocational education studies and offering practical recommendations for media integration.